USING TABLES TO BUILD A MATHEMATICAL MODEL IN PROBLEMS WITH ECONOMIC CONTENT - Рынков, Анна (SWorldJournal, 2020)
The paper considers the use of tables as a universal method for constructing a mathematical model in problems with economic content. The author substantiates the possibility of using this approach to solve problems of any complexity and various schemes (